JS-NG-10: A RARE CAUSE OF TREATMENT-RESISTANT HYPERTENSION. (January 2023) - Hausberg, Martin; Seitz, Karl Heinz; Teber, Dogu; Reimer, Peter; Rueciger, Thomas
Abstract : Objective: To present an educational case report. Design and method: In a 22-year old female arterial hypertension was diagnosed and she was treated to blood pressure target values with a combination of candesartan and lercanidipine. At the age of 27 years she planned a pregnancy, therefore antihypertensive treatment was switched to alpha-methyl-dopa and metoprolol. Blood pressure control was no longer achieved, the patient was symptomatic, mostly headaches. A diagnostic work-up for secondary causes of hypertension was performed. Results: There were no signs of kidney disease, renal artery stenosis was ruled out by color-coded duplex-ultrasound, plasma metanephrines were normal, sleep apnea syndrome and hypercortisolism were clinically very unlikely and not formally ruled out. No signs of hypertensive end-organ damage (left ventricular hypertrophy, microalbuminuria, carotid artery alterations) were detected. The only pathologic finding confirmed was a marked secondary hyperaldosteronism. Plasma renin concentration was 230 pg/ml, plasma aldosterone concentration 508 pg/ml, along with low normal serum potassium (3.5 to 4 mmol/l). Addition of nifedipine and low-dose HCT did not achieve blood pressure control, daytime ABPM mean was 144/102 mmHg, nighttime ABPM mean 127/86 mmHg. Because of suspected missed renal artery stenosis (fibromuscular dysplasia) an MR-angiography of the renal arteries was performed revealing normal renal arteries and normal adrenal glands but a left kidney tumor - not observed in the previous ultrasound examination but confirmed with contrast-enhanced ultrasound. Surgical removal of the tumor was performed. The histology was suggestive for a juxtaglomerular cell tumor (reninoma). After surgery, plasma aldosterone normalized to 57 pg/ml and plasma renin concentrations were low (3.4 pg/ml). Within 3 months after surgery, all antihypertensive medication could be discontinued and home blood pressure measurements averaged 119/78 mmHg. Soon thereafter the patient became pregnant and delivered a healthy girl. There were no pregnancy related complications and the patient remained normotensive. A juxtaglomerular cell tumor represents a rare curable cause of hypertension. The first report dates for 1967, until 2019 only about 100 cases were reported in the literature. It may be suspected that the diagnosis juxtaglomerular cell tumors is missed in many cases since these tumors are not easy to detect in standard diagnostic workup of hypertension and many antihypertensive drugs interfere with plasma renin concentrations.